The Relationship Between Pediatric Residents' Experiences Being Parented and Their Provision of Parenting Advice - Bax, Ami C.; Shawler, Paul M.; Anderson, Michael P.; Wolraich, Mark L. (Frontiers in Pediatrics, 2018)
Background: Factors surrounding pediatricians’ parenting advice and training on parenting during residency have not been well studied. The Resident Parenting Questionnaire was developed to assess a) the relationship between pediatric residents’ upbringing and their parenting advice style and b) factors associated with confidence and resource use when delivering parenting advice. Methods: 301 pediatric residents from 15 United States residency programs completed the Resident Parenting Questionnaire with upbringing and advice responses categorized using Baumrind’s parenting model (authoritative, authoritarian, permissive). Chi-square/Fisher’s exact tests, Bowker’s test of symmetry, and regression analyses assessed associations between residents’ upbringing, parenting advice style/content, and confidence in providing parenting advice. Results: Most participants indicated being raised authoritatively (68%) and giving authoritative parenting advice (83%), but advice differed based on how they perceived their upbringing (p<0.0001). Residents noting authoritative upbringing were more likely to give authoritative advice (85%) while others tended to give advice differing from upbringing (e.g. those perceiving authoritarian upbringing were more likely to give authoritative/permissive). Analyses suggest resident race, acculturation, future plans, and resident level are associated with parenting advice type. Confidence in giving parenting advice decreased significantly as patient age increased and increased with resident level advancement. Residents reported consulting attending physicians for parenting advice guidance more than any other evidence-based resources. Conclusion: Most pediatric residents appear to be aware of appropriate authoritative parenting advice regardless of upbringing, especially as they advance through residency. Residents may benefit from opportunities to reflect upon their upbringing, particularly if raised in authoritarian or permissive styles. Targeted training of residents on evidence-based parenting strategies, particularly for older pediatric patients, appears warranted.